Arkansas Rice: Herbicide Resistance Concerns, Production Practices, and Weed Management Costs - Butts, Thomas R.; Kouame, K. Badou-Jeremie; Norsworthy, Jason K.; Barber, L. Tom (Frontiers in Agronomy, 2022)
An online survey to better understand current weed management practices and concerns in Arkansas rice was distributed in the fall of 2020. A total of 123 respondents from across the Arkansas rice growing region returned the survey covering a total of 236,414 rice hectares, representing about 40% of the planted Arkansas rice hectares in 2020. The most problematic weeds were Echinochloa crus-galli (L.) P. Beauv. (ECG), Cyperus spp., and Oryza sativa L. (weedy rice), respectively, in flooded rice, and ECG, Amaranthus palmeri S. Wats., and Cyperus spp., respectively, in furrow-irrigated rice. Most respondents (78%) reported high concern with herbicide-resistant weeds, and crop rotation (>74%) was the most common strategy listed to control and mitigate the development of herbicide-resistant weeds. A chi-square test of homogeneity showed that strategies implemented to control herbicide-resistant weeds and mitigate the evolution of herbicide-resistant weeds were not dependent on occupation type (farmer, consultant, or industry rep) nor on years of involvement in rice production. Respondents failed to control ECG 44% of the time with their first postemergence herbicide. After initial herbicide failure, 53% of respondents stated two additional herbicide applications were required to control ECG escapes while another 21% of respondents stated it was never controlled. The average ECG population at 2020 harvest was between 0.1 and 1.0 plant m-2 according to 44% of the respondents; however, 41% of respondents indicated a ECG density of 2 to 10 plants m-2 at 2020 harvest. The reported annual average cost of herbicides for rice weed control was $266.40 ha-1 with ECG accounting for 81% of the total cost. Average yield loss attributed to ECG was estimated to be 505 to 959 kg ha-1 (economic loss of $134 to $254 ha-1). However, yield loss in the most heavily infested fields was estimated to be 757 to 1464 kg ha-1 (economic loss of $200 to $387 ha-1). Effective, non-chemical approaches to weed management were ranked as the least important current research or educational effort, indicating a paradigm shift in rice producers’ weed control line of thought is needed with dwindling herbicide options due to herbicide resistance.